2013
DOI: 10.1027/0227-5910/a000168
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of School-Based Interventions Aimed at Preventing, Treating, and Responding to Suicide- Related Behavior in Young People

Abstract: The most promising interventions for schools appear to be gatekeeper training and screening programs. However, more research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(174 citation statements)
references
References 78 publications
3
147
0
17
Order By: Relevance
“…This finding is supported by studies that reported a recent decline in suicide rates [48][49][50] and attempts 51 among Canadian and American youth. Though there is no conclusive evidence for the efficacy of various efforts in preventing suicide, 52 some strategies, including physician education and certain school-based strategies, show promise in reducing suicidal behaviours. 46,47,50,53 Continued effort in suicide prevention, rigorous research into the efficacy of prevention programs, and improved interventions targeting mental illness in adolescents is crucial for improving the mental health of Canadian adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is supported by studies that reported a recent decline in suicide rates [48][49][50] and attempts 51 among Canadian and American youth. Though there is no conclusive evidence for the efficacy of various efforts in preventing suicide, 52 some strategies, including physician education and certain school-based strategies, show promise in reducing suicidal behaviours. 46,47,50,53 Continued effort in suicide prevention, rigorous research into the efficacy of prevention programs, and improved interventions targeting mental illness in adolescents is crucial for improving the mental health of Canadian adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Generell kunnskap om psykiske vansker som angst og depresjon, personlig og profesjonell erfaring som kan bidra til økt trygghet i rollen, bevissthet om egne holdninger til selvmord samt indre motivasjon for å hjelpe, blir alle vurdert som relevante kvaliteter for å inneha en slik funksjon (King & Smith, 2000). Opplaeringen vektlegger kunnskap og ferdigheter i å kunne identifisere elever med forhøyet risiko for selvmord eller selvskading, gjennomføre avdekkende samtaler, og utrede omfang og alvorlighetsgrad for eventuelt å kunne henvise til profesjonell helsehjelp (Robinson et al, 2013;De Silva, Parker, Purcell, Callahan, Liu & Hetrick, 2013). Både teoretisk kunnskap og praktiske ferdigheter må innarbeides og innøves gjennom hele kjeden av formidling.…”
Section: Portvaktmodellen Og «Train-the-trainer»unclassified
“…It should be noted that there is a lack of consensus as to whether non-suicidal selfharm behaviour should be included in reviews that focus on suicidal behaviour (Halicka and Kiejna, 2015). The Robinson review also suggested that there was limited evidence that school-based interventions reduce suicidal behaviour and ideation itself (Robinson et al, 2013). Universal prevention approaches demonstrated some effects, while indicated prevention interventions showed promise (Robinson et al, 2013) and require further evaluation.…”
Section: Direct Intervention For Adolescent Suicidalitymentioning
confidence: 99%
“…The Robinson review also suggested that there was limited evidence that school-based interventions reduce suicidal behaviour and ideation itself (Robinson et al, 2013). Universal prevention approaches demonstrated some effects, while indicated prevention interventions showed promise (Robinson et al, 2013) and require further evaluation.…”
Section: Direct Intervention For Adolescent Suicidalitymentioning
confidence: 99%
See 1 more Smart Citation